Jesus as a Wounded Woman: A Postcolonial Feminist Trauma Reading of Emanuel Garibay's Emmaus - Donald Steven Keryapi; Rosnita Temba Kagu (Jurnal Theologia, 2025)
This article uses Emanuel Garibay's painting "Emmaus" as the primary unit of analysis to construct a theological understanding of Jesus as a wounded woman within the framework of postcolonial feminist trauma theology. This research aims to examine how visual art can function as an alternative theological space to reimagine Christology in responding to the experiences of trauma and sexual violence experienced by women. Methodologically, this study uses Erwin Panofsky's three-stage art analysis—pre-iconography, iconography, and iconology—integrated with postcolonial feminist trauma hermeneutics. The study's findings reveal that the Emmaus painting depicts Jesus as a wounded female figure, where the wounded body serves as a symbol of trauma, resistance, and solidarity with marginalized women. This reading offers a novelty in the form of a Christological metaphor that extends theological reflection beyond the biblical text into the realm of theological aesthetics. This article contributes to the global discourse of trauma theology and feminist Christology by affirming visual art as a constructive medium for the articulation of recovery, the existence of the body, and the formation of a community of survivors of sexual violence.